PENERAPAN HUKUM DALAM PENYELESAIAN SENGKETA TRANSAKSI ELEKTRONIK DI PERADILAN UMUM - Rahadi Wasi Bintoro (Jurnal Dinamika Hukum, 2011)
This research is study about law construction of forming electronic contract in transaction that exploiting information technology and law of evidence that applying for electronic document. and to explaing its, researcher use statue approach, conceptual approach and case approach, that is included in the approach method in legal research. Pursuant to research which have been done, agreement  in e-commerce is form when there is an acceptance from buyer by electrically or when the buyer signing a digital signature. Evidence law of electronic document that form in e-commerce and e-banking have strength of  perfect verification as pukka act, as long as it is using security system which is difficult technically to be able to infiltrate or leaked by other party, while  electronic document from transfer of company document to electronic media have strength of perfect verification. In the case of dispute in e-commerce, e-banking  dispute and dispute of company document which have been transferred in the form of electronic media, hence can be raised by evidence appliance in the form of written evidence appliance, eyewitness, presupposition, confession, oath, and expert eyewitness to strengthen electronic document. But that way, rule of law not yet been given by comprehensively.  Keywords : internet, e-commerce, e-banking, company documen, evidence law